Functional analysis of MEIS2 splice site variant c.438 + 1G>T in a congenital heart patient - Xu, Chenyu; Li, Junjuan; Ma, Xinghui; Li, Wenqi; Jiang, Bo; Bai, Hua; Wu, Fuhong; Liu, Chunlian; Gu, Jiwei (Frontiers in Genetics, 2025)
AimsMEIS2 (NCBI:4212; OMIM:601740) is associated with cleft palate, atrial septal defect, and varying degrees of intellectual disability. The aim of this study is to investigate the value of minigene splicing assay in the diagnosis of congenital heart disease (CHD) with mental retardation, and to explore the impact of a novel splicing-site variant on the transcript products of the MEIS2 homeobox 2 (MEIS2) gene.MethodsTo identify disease-causing mutations, we performed whole-exome sequencing (WES) of affected family members and subsequently employed a minigene splicing assay to evaluate the functional impact of the MEIS2 gene splicing variant.Results1. Postoperative transesophageal ultrasound observation of the proband showed a satisfactory umbrella shape, no shunt or displacement, and normal opening and closing of each valve; 2. WES identified a heterozygous c.438 + 1G>T variant in the intronic region of the MEIS2 gene, which was a de novo mutation confirmed by Sanger sequencing; 3. The results of the minigene splicing assay showed that c.438 + 1G>T affected the normal splicing of precursor mRNA. This was demonstrated consistently by constructing pcDNA3. 1 and pcMINI-C vectors. Two aberrant splicing modes were identified after the mutation: ① Retention of 290 bp in intron4, resulting in a frameshift and the introduction of a premature termination codon (PTC) within the retained fragment, predicted to produce a truncated protein of 175 aa (p.Met147Leufs*30); ② Exon4 skipping, represented at the cDNA and protein levels as c.388_438del p. Val130_Leu146del, which did not cause a frameshift but led to an internal deletion of 17 aa within the protein, predicted to result in a truncated protein of 460 aa.ConclusionsMinigene splicing assay revealed a new molecular marker for the definitive diagnosis and genetic counseling of CHD. Functional analysis to verify intronic pathogenicity has important diagnostic value. The study expanded the MEIS2 genetic spectrum and provided laboratory evidence for clinical diagnosis and treatment.